Potensi Nanofiltrasi dalam Pemekatan Bakteri Asam Laktat sebagai Probiotik Savory dari Kacang Hijau (Phaseolus radiatus L.) Terfermentasi oleh Rhizopus-C - Sri Moerniati; Agustine Susilowati; Aspiyanto Aspiyanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Concentration of fermented Mung beans as ingredient probiotic through Nanofiltration at fixed pump motor frequency and pressure for long time was an important effort to reach optimal operation condition, so it is generated savory functional product with the best total LAB count and composition. Concentration process of fermented Mung beans substrates by Rhizopus-C fermented by LAB using mixed cultures of L. bulgaricus and S. thermophilus and enriched by full cream milk at 40 °C for 48 hours was performed at pump motor frequency of 20 Hz, room temperature and pressure of 25 bar for 30, 60, 90, 120, 150, 180, 210, 240, 270 and 300 minutes, respectively. The result of activity demonstrated that long time of concentration process would reduce permeate flux, increased retentate composition of total LAB count, total solids, total acids, dissolved protein and reducing sugar, while salt concentration would be de- clined. Based on total LAB count and process efficiency, optimal time of concentration to generate retentate as savory probiotic was 210 minutes with concentrations of total solids of 21.25 %, total acids of 1.35 %, dissolved protein of 5.65 mg/mL, reducing sugar of 127.5 mg/mL, salt of 0.57 % and total LAB count of 2.6 x 1010 cfu/mL, whereas permeate as side product could be used as probiotic acidulent gave flux of 9 L/m2.hour with concentrations of total solids of 2.24%, total acids of 1.24 %, dissolved protein of 0.02 mg/mL, reducing sugar of 2.985 mg/mL, salt of 0.67 % and totalLAB count of 1.2 x 107 cfu/mL.ABSTRAKPemekatan konsentrat kacang hijau terfermentasi sebagai probiotik ingredient menggunakan sistem nanofiltrasi den- gan waktu yang semakin meningkat pada tekanan & kecepatan motor tetap merupakan upaya untuk memperoleh kon- disi operasi optimal sehingga dihasilkan produk fungsinal savory dengan total BAL dan komposisi terbaik. Proses pemekatan dilakukan selama 30, 60, 90, 120, 150 ,180, 210, 240, 270 dan 300 menit, tekanan 25 bar, frekwensi motor pompa 20 Hz, suhu ruang pada substrat kacang hijau terfermentasi oleh Rhizopus C yang difermentasi oleh BAL pada suhu 40 °C selama 48 jam menggunakan campuran L. bulgaricus dan S. thermophilus dan diperkaya dengan susu skim. Hasil penelitian menunjukkan bahwa peningkatan waktu proses akan menurunkan fluks bahan namun meningkatkan komposisi retentat terhadap total BAL, total solid, total asam, protein terlarut, gula pereduksi sedangkan kadar garam cenderung menurun. Berdasarkan jumlah BAL dan efesiensi proses, Waktu pemekatan 210 menit adalah optimal dalam dalam menghasilkan retentat sebagai probiotik savory dengan total padatan kering 21,25 %, total asam 1,35 %, protein terlarut 5,65 mg/mL, gula pereduksi 127,5 mg/mL, garam 0,57 % dan jumlah BAL 2,6 x 1010 cfu/mL dan fluks permeat 9L/m2.jam sedangkan permeat sebagai produk samping yang berpotensi sebagai acidulant berprobiotik dengan kandun-gan total padatan kering 2,24 %, total asam 1,24 %, protein terlarut 0,02 mg/mL, gula pereduksi 2,985 mg/mL, garam0,67 % dan jumlah BAL 1,2 x 107 cfu/ml.